Luminescent ceramic, preparation method, wavelength conversion device and light-emitting device

By setting up the structure of fluorescent powder, fluorescent covering layers, matrix ceramic grains and air holes in the luminous ceramics, it solves the problem of difficulty in taking into account multiple performance under high -power laser lighting. Efficiency and thermal conductivity.

CN119371182APending Publication Date: 2025-01-28YLX INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310901349.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-20
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

It is difficult for luminescent ceramics to take into account both luminescent efficiency, light extraction efficiency, thermal saturation performance and light saturation performance under high-power laser illumination.

Method used

By setting up fluorescent powder grains, fluorescent covering layers, matrix ceramic grains and air holes in the luminous ceramics, the fluorescent cover layer is wrapped in the peripheral peripheral of fluorescent powder grains. The combination of grains is located between the matrix ceramic grains and the fluorescent cover layer or between multiple matrix ceramic grains.

Benefits of technology

It improves the light extraction efficiency and thermal conductivity of light -emitting ceramics, enhances its reliability shown under high -power laser, and takes into account lighting efficiency, light extraction efficiency, thermal saturation performance and light saturation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371182A_ABST
    Figure CN119371182A_ABST
Patent Text Reader

Abstract

The invention discloses light-emitting ceramic, a preparation method, a wavelength conversion device and a light-emitting device. The light-emitting ceramic comprises fluorescent powder crystal grains, a fluorescent coating layer, matrix ceramic crystal grains and air holes, the fluorescent coating layer is enveloped on the periphery of the fluorescent powder crystal grains, and at least part of the fluorescent powder crystal grains are combined with the matrix ceramic crystal grains through the fluorescent coating layer; at least part of the air holes are located between the matrix ceramic crystal grains or / and between the matrix ceramic crystal grains and the fluorescent coating layer. By arranging the fluorescent powder crystal grains, the fluorescent coating layer, the matrix ceramic crystal grains and the air holes, the luminous efficiency, the luminous efficiency, the thermal saturation and the light saturation performance of the luminous ceramic are considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of luminescent ceramic material preparation, and in particular to a luminescent ceramic, a preparation method, a wavelength conversion device and a light-emitting device. Background Art

[0002] Laser lighting technology has the advantages of high brightness, long irradiation distance, higher conversion efficiency and longer service life. In the near future, laser lighting may replace the current LED lighting and set off a new round of lighting technology revolution.

[0003] At present, the mainstream technology in the field of laser light sources has gradually developed into blue laser excitation of fluorescent materials to achieve wavelength conversion and obtain white light, but traditional yellow, green and red phosphors are difficult to achieve stable luminescence under continuous irradiation of high-intensity lasers. In recent years, with the rapid development of luminescent ceramics, luminescent ceramics are regarded as one of the most suitable fluorescent materials for high-power laser lighting due to their excellent luminescence and thermal shock resistance. However, as the laser power becomes higher and higher, in addition to the thermal shock of high power density, luminescent ceramics are also subjected to irradiation with high optical power density. Therefore, luminescent ceramics are not only required to have excellent luminescence efficiency, but also excellent light extraction efficiency, thermal saturation performance and light saturation performance. This puts forward higher requirements on the balance of light extraction efficiency, light efficiency, thermal saturation performance and light saturation performance of luminescent ceramics. Summary of the invention

[0004] In view of this, the present application provides a luminescent ceramic and a preparation method to solve the problem of the difficulty in balancing the luminescent efficiency, light extraction efficiency, thermal saturation performance and light saturation performance of the luminescent ceramic.

[0005] The present application proposes a luminescent ceramic, comprising phosphor grains, a phosphor coating layer, matrix ceramic grains and pores; the phosphor coating layer envelops the periphery of the phosphor grains, and at least part of the phosphor grains is combined with the matrix ceramic grains through the phosphor coating layer; at least part of the pores are located between multiple matrix ceramic grains or / and between the matrix ceramic grains and the phosphor coating layer.

[0006] Optionally, the fluorescent coating layer includes a first matrix phase doped with a first luminescent ion; the fluorescent powder grains include a second matrix phase doped with a second luminescent ion; the first luminescent ion is the same as or different from the second luminescent ion; or / and the first matrix phase is the same as or different from the second matrix phase.

[0007] Optionally, the molar doping concentration of the first luminescent ion is 0.02% to 5%; or / and the molar doping concentration of the second luminescent ion is 0.01% to 10%.

[0008] Optionally, the molar doping concentration of the first light-emitting ions is less than the molar doping concentration of the second light-emitting ions.

[0009] Optionally, the first matrix phase and the second matrix phase are oxide garnet phases; and the first luminescent ions and the second luminescent ions are cerium ions.

[0010] Optionally, the volume content of the phosphor particles is 30% to 90%;

[0011] Or / and the particle size of the phosphor crystal particles is 1 to 10 um.

[0012] Optionally, the percentage of pores in the total volume of the luminescent ceramic is 5 to 10%;

[0013] Or / and the pore size is 0.4~1um.

[0014] The present application also proposes a method for preparing a luminescent ceramic, the preparation method comprising:

[0015] preparing raw materials for a fluorescent coating layer, mixing, sintering and crushing the raw materials for the fluorescent coating layer to obtain a fluorescent coating layer powder;

[0016] Preparing phosphor crystals, mixing the phosphor crystals with phosphor coating layer powder to obtain coated phosphor crystals;

[0017] preparing a matrix ceramic powder and a sintering aid, mixing, molding and pre-sintering the coated phosphor grains, the matrix ceramic powder and the sintering aid to obtain a first sintered body;

[0018] Sintering the first sintered body to obtain a luminescent ceramic block;

[0019] The luminescent ceramic block is annealed and surface treated to obtain the luminescent ceramic.

[0020] The present application also provides a wavelength conversion device, which includes a luminescent ceramic layer, wherein the luminescent ceramic layer is made of the above luminescent ceramic.

[0021] The present application also proposes a light-emitting device, which includes an excitation light source and a wavelength conversion device.

[0022] The beneficial effects of the present application are as follows: different from the prior art, the present application sets phosphor grains, a phosphor coating layer, a matrix ceramic grains and pores, sets the phosphor coating layer to envelop the periphery of the phosphor grains, sets at least part of the phosphor grains to be combined with the matrix ceramic grains through the phosphor coating layer, sets at least part of the pores to be located between multiple matrix ceramic grains, and / or sets the pores to be located between the matrix ceramic grains and the phosphor coating layer. The present application sets a fluorescent coating layer connected to the matrix ceramic grains, and the difference in refractive index between the fluorescent coating layer and the matrix ceramic grains will cause the incident excitation light to scatter, which can improve the light extraction efficiency of the luminescent ceramic, and can use the fluorescent coating layer to maintain efficient absorption and conversion of the excitation light to achieve high luminous efficiency; the present application sets pores between multiple matrix ceramic grains, or sets pores between the matrix ceramic grains and the fluorescent coating layer, so that the presence of pores can increase light scattering and improve the light extraction efficiency of the luminescent ceramic; in addition, the matrix ceramic grains around the phosphor grains can also effectively improve the thermal conduction and diffusion of the fluorescent ceramic, and can obtain a higher thermal saturation threshold, showing higher reliability under high power density excitation light excitation. Therefore, the luminescent ceramic of the present application takes into account the luminous efficiency, light extraction efficiency, thermal saturation and light saturation performance.

[0023] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0025] Figure 1 This is a schematic structural diagram of an embodiment of the luminescent ceramic of the present application;

[0026] Figure 2 This is a scanning electron microscope magnified image of an embodiment of the luminescent ceramic of the present application;

[0027] Figure 3 This is a scanning electron microscope magnified image of an embodiment of the luminescent ceramic of the present application;

[0028] Figure 4 It is a flow chart of an embodiment of the preparation method of the present application;

[0029] Figure 5 yes Figure 4 Step S100 and step S200 and a specific flow chart;

[0030] Figure 6 yes Figure 4 Specific flow chart of step S300. DETAILED DESCRIPTION

[0031] In order to enable those skilled in the art to better understand the technical solution of the present application, the luminescent ceramics and preparation methods provided by the present application are further described in detail below in conjunction with the accompanying drawings and specific implementation methods. It can be understood that the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0032] The terms "first", "second", etc. in this application are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.

[0033] The present application provides a luminescent ceramic, a preparation method, a wavelength conversion device and a luminescent device to solve the problem that it is difficult to balance the luminescent efficiency, light extraction efficiency, thermal saturation performance and light saturation performance of the luminescent ceramic.

[0034] See also Figures 1 to 6 , Figure 1 This is a schematic structural diagram of an embodiment of the luminescent ceramic of the present application; Figure 2 This is a scanning electron microscope magnified image of an embodiment of the luminescent ceramic of the present application; Figure 3 This is a scanning electron microscope magnified image of an embodiment of the luminescent ceramic of the present application; Figure 4 It is a flow chart of an embodiment of the preparation method of the present application; Figure 5 yes Figure 4 Specific flow chart of step S100 and step S200; Figure 6 yes Figure 4 Specific flow chart of step S300.

[0035] The present application provides a luminescent ceramic. In one embodiment, Figure 1As shown, the luminescent ceramic includes phosphor grains 10, a phosphor coating layer 30, a matrix ceramic grain 40 and pores 20. The phosphor coating layer 30 may be encapsulated on the periphery of the phosphor grains 10, and encapsulation means that the phosphor grains 10 are wrapped and covered on all or part of the outer surface, and part or all of the phosphor grains 10 may be combined with the matrix ceramic grains 40 through the phosphor coating layer 30. The matrix ceramic grains 40 may be connected to the phosphor coating layer 30 and combined with the phosphor coating layer 30. Part or all of the pores 20 may be located between a plurality of matrix ceramic grains 40, or / and part or all of the pores 20 may also be located between the matrix ceramic grains 40 and the phosphor coating layer 30.

[0036] It can be understood that by setting the fluorescent coating layer 30 on the periphery of the phosphor crystal grains 10, the fluorescent coating layer 30 wraps the phosphor crystal grains 10. When the materials of the fluorescent coating layer 30 and the matrix ceramic are different, there is a difference in the refractive index of the fluorescent coating layer 30 and the matrix ceramic crystal grains 40, so that the incident excitation light is scattered, the propagation path changes, and the light extraction efficiency is improved. And the fluorescent coating layer 30 can emit light together with the phosphor crystal grains 10 under the excitation of the excitation light, thereby improving the absorption rate of the incident light, and then maintaining the efficient absorption and conversion of the incident light, and achieving high luminous efficiency. Secondly, the matrix ceramic crystal grains 40 are connected to the fluorescent coating layer 30, so that the heat generated by the phosphor crystal grains 10 and the fluorescent coating layer 30 can be conducted to the matrix ceramic crystal grains 40, so that the matrix ceramic crystal grains 40 close to the fluorescent coating layer 30 can effectively improve the thermal conduction and diffusion of the fluorescent ceramic, obtain a higher thermal saturation threshold, and show higher reliability under the excitation of high power density excitation light. In addition, the pores 20 are retained between the matrix ceramic grains 40 and the fluorescent coating layer 30 or between multiple matrix ceramic grains 40, which can also improve the scattering of the excitation light, thereby improving the light extraction efficiency of the luminescent ceramic. Due to the improvement of the luminous efficiency and thermal saturation performance of the fluorescent ceramic, the light saturation threshold can be finally improved.

[0037] In some embodiments, Figure 1 As shown, the fluorescent coating layer 30 may include a first matrix phase doped with a first luminescent ion, and the phosphor crystal grains 10 may include a second matrix phase doped with a second luminescent ion. The first luminescent ion and the second luminescent ion may be rare earth ions or transition metal ions, such as Mn (manganese), Ce (cerium), Eu (europium), Yb (ytterbium), Nd (neodymium), Gd (gadolinium), Sm (samarium), Tb (terbium), Dy (dysprosium), Ho (holmium), Er (erbium), Tm (thulium), etc.; the first matrix phase and the second matrix phase may be aluminates, silicates, tungstates, phosphates, nitrides, etc.

[0038] Among them, the first luminescent ion and the second luminescent ion can be the same or different, or / and the first matrix phase and the second matrix phase can be the same or different. When the first luminescent ion and the second luminescent ion are the same, the fluorescent coating layer 30 can be used as a fluorescence enhancement phase, that is, the excitation light can pass through the fluorescent coating layer and be incident on the phosphor grains. At this time, the fluorescent coating layer 30 and the phosphor grains 10 can be excited to produce fluorescence at the same time, and the luminescent color is the same, and the luminous efficiency is improved at this time. When the first luminescent ion and the second luminescent ion are different, or when the first matrix phase and the second matrix phase are different, it can be used as a color complementary phase, that is, the wavelength of the fluorescence produced by the fluorescent coating layer and the phosphor grains being excited is different. At this time, the fluorescent coating layer can supplement or adjust the luminescent spectrum of the phosphor grains.

[0039] In some embodiments, the first matrix phase and the second matrix phase are oxide garnet phases, and the first luminescent ion and the second luminescent ion are cerium ions. Optionally, the first luminescent ion is cerium ion, the first matrix phase is oxide garnet phase, and cerium ions are doped in the oxide garnet phase to form a fluorescent coating layer 30. Optionally, the second luminescent ion is cerium ion, the second matrix phase is oxide garnet phase, and cerium ions are doped in the oxide garnet phase to form phosphor grains 10. As an example, cerium ions can be doped in Y 3 Al 5 O 12 (yttrium aluminate, abbreviated as YAG) or Lu 3 Al 5 O 12 (lutetium aluminum garnet, abbreviated as LuAG) or Gd 3 (Al,Ga) 5 O 12 (cerium-doped gadolinium gallium aluminate, abbreviated as GAGG) etc. It can be understood that the composition of the oxide garnet phase of the first matrix phase and the second matrix phase can be the same or different.

[0040] In some embodiments, the molar doping concentration of the first luminescent ion is 0.01% to 10%, and further can be 0.02% to 5%, which can be used as the fluorescence efficiency enhancement phase of the phosphor crystal 10 or the color complementary phase of the phosphor crystal 10. The molar doping concentration of the first luminescent ion can also be set to 0.02%, 0.1%, 0.5%, 0.8%, 1%, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% and 10%; or / and the molar doping concentration of the second luminescent ion is 0.01% to 10%, and the molar doping concentration of the second luminescent ion can also be set to 0.02%, 0.1%, 0.5%, 0.8%, 1%, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% and 10%. If the amount of the luminescent ion is too small, the luminescent intensity of the luminescent ceramic is weak. If the amount of the luminescent ion is too much, concentration quenching is likely to occur, and the luminescent intensity tends to decrease.

[0041] In the present application, the molar doping concentration of the first luminescent ion and the second luminescent ion may be the same or different. In some embodiments, the molar doping concentration of the first luminescent ion is less than the molar doping concentration of the second luminescent ion. Since the phosphor crystal grains 10 are the main material for light conversion and have a high luminous efficiency, the excitation light needs to pass through the fluorescent coating layer 30 to enter the phosphor crystal grains 10. By making the doping concentration of the fluorescent coating layer 30 lower than the doping concentration of the phosphor crystal grains 10, the fluorescent coating layer 30 plays a role in supplementing or enhancing the luminescence of the phosphor crystal grains 10, so that the luminescent ceramic obtains the best overall luminous efficiency.

[0042] In some embodiments, the volume content of the phosphor crystal grains 10 is 30% to 90%. The volume content of the phosphor crystal grains can also be set to 30%, 40%, 50%, 60%, 70%, 80%, 90% or any value between the above two values. It should be noted that the volume content is the percentage of the phosphor crystal grains 10 in the total volume of the luminescent ceramic. When the volume content of the phosphor crystal grains 10 is in the range of 30% to 90%, a high luminous intensity can be maintained. If the volume content of the phosphor crystal grains 10 is less than 30%, the phosphor crystal grains 10 used for light conversion are less, and the overall luminous intensity of the luminescent ceramic is lower. If the volume content of the phosphor crystal grains 10 is greater than 90%, the content of the matrix ceramic crystal grains 40 used for heat conduction is less, which is easy to cause thermal quenching of the luminescence, reduce the thermal saturation performance, and is also not conducive to improving the luminous intensity.

[0043] Optionally, the particle size of the phosphor crystal particles 10 is 0.2-20 μm, and the particle size of the phosphor crystal particles 10 is preferably 1-10 μm. The particle size of the phosphor crystal particles 10 can also be set to 0.2 μm, 0.5 μm, 0.8 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 12 μm, 15 μm, 16 μm, 18 μm, 20 μm or any value between the above two values.

[0044] In some embodiments, the pores 20 are closed pores 20 at grain boundaries caused by non-density during sintering or volatilization of additives, and the pores 20 are evenly distributed in the luminescent ceramic, and multiple pores 20 are independent of each other. The pores 20 can improve the light scattering ability of the luminescent ceramic, and can further enhance the absorption of scattered excitation light in the phosphor grains 10, which effectively improves the light extraction efficiency.

[0045] Optionally, if the percentage of the volume of the pores 20 is too small, a good scattering effect cannot be achieved, but if the percentage is too large, the mechanical strength of the luminescent ceramic will be reduced, and the heat dissipation capacity of the luminescent ceramic will also be affected. Therefore, the percentage of the pores 20 to the total volume of the luminescent ceramic is set to 2-20%, and the percentage of the pores 20 to the total volume of the luminescent ceramic is preferably 5-10%. The percentage of all pores 20 to the total volume of the luminescent ceramic can also be 2%, 3%, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 13%, 15%, 16%, 18%, 20%, or any value between two adjacent values ​​mentioned above.

[0046] Optionally, the aperture size of the pore 20 is 0.1-2um, and further can be 0.4-1um. The aperture size of the pore 20 can also be set to 0.1um, 0.2um, 0.4um, 0.5um, 0.6um, 0.7um, 0.8um, 0.9um, 1.0um, 1.2um, 1.4um, 1.6um, 1.8um, 2um or any value between the above two values. Pores that are too large or too small are not conducive to improving the scattering effect. The introduction of pores of appropriate particle size can further improve the scattering performance of the luminescent ceramic to light and further improve the light extraction efficiency.

[0047] In some embodiments, the matrix ceramic grains 40 may be high thermal conductivity ceramic grains, for example, may include aluminum oxide (Al 2 O 3 ), magnesium oxide (MgO), magnesium aluminate (MgAl 2 O 4 ), one or more of boron nitride (BN) and aluminum nitride (AIN).

[0048] The present application also proposes a method for preparing a luminescent ceramic, such as Figure 4As shown, the preparation method for preparing the luminescent ceramic of any of the above embodiments includes:

[0049] Step S100: preparing raw materials for the fluorescent coating layer, mixing, sintering and crushing the raw materials for the fluorescent coating layer to obtain fluorescent coating layer powder.

[0050] like Figure 5 As shown, step S100: preparing raw materials for the fluorescent coating layer, mixing, sintering and crushing the raw materials for the fluorescent coating layer, and obtaining the fluorescent coating layer powder comprises:

[0051] Step S110: preparing raw materials for the fluorescent coating layer, and ball-milling the raw materials for the fluorescent coating layer and the additives to uniformly mix to form a first slurry;

[0052] Step S120: calcining the first slurry into a phase, and then grinding and sieving to form a fluorescent coating layer powder.

[0053] Among them, the fluorescent coating layer is YAG:Ce 3+ For example, the oxide raw material can be nano-scale Al 2 O 3 , Y 2 O 3 、Ce 2 The additive may include a sintering aid and a ball milling aid, such as one or more of ethanol, PEG, tetraethyl orthosilicate, silicon dioxide, magnesium oxide, boric acid, calcium carbonate, lithium fluoride, etc. The calcination temperature may be, for example, 1100-1700° C., and the calcination time may be, for example, 1-5 hours.

[0054] Step S200: preparing phosphor particles, and mixing the phosphor particles with phosphor coating layer powder to obtain coated phosphor particles.

[0055] Step S200: preparing phosphor crystal particles, mixing the phosphor crystal particles with the phosphor coating layer powder, and obtaining the coated phosphor crystal particles comprises:

[0056] Step S210: preparing phosphor particles, mixing and stirring the coating layer powder, phosphor particles and a binder to form a second slurry;

[0057] Step S220: vacuum drying the second slurry to obtain coated phosphor powder.

[0058] The binder may be a polymer resin, and the amount of the binder added may be 0.001 vol% to 5 vol% of the total volume of the coating layer powder and the phosphor particles.

[0059] Step S300: preparing a matrix ceramic powder and a sintering aid, mixing, molding and pre-sintering the coated phosphor grains, the matrix ceramic powder and the sintering aid to obtain a first sintered body.

[0060] like Figure 6 As shown, step S300: preparing a matrix ceramic powder and a sintering aid, mixing, molding and pre-sintering the coated phosphor grains, the matrix ceramic powder and the sintering aid, and obtaining a first sintered body includes:

[0061] Step S310: mixing the prepared coated phosphor powder, matrix ceramic powder and sintering aid, drying, grinding and sieving to obtain a mixed powder;

[0062] Step S320: calcining the mixed powder and dry pressing it to obtain a ceramic body;

[0063] Step S330: pre-sintering the ceramic body to obtain a first sintered body.

[0064] The calcination temperature may be, for example, 800-1000°C, and the calcination time may be, for example, 1-3 hours. The molding may be, for example, dry pressing or cold isostatic pressing, the pressure of dry pressing may be 5-50 MPa, and the pressure of cold isostatic pressing may be 50-250 MPa. The sintering aid may be, for example, one or more of calcium fluoride, magnesium oxide, calcium oxide, yttrium oxide, silicon dioxide, etc. The pre-sintering temperature may be 900-1100°C, and the pre-sintering time may be, for example, 1-5 hours.

[0065] Step S400: sintering the first sintered body to obtain a luminescent ceramic block.

[0066] The first sintered body is sintered in a vacuum or protective atmosphere. The sintering temperature may be, for example, 1300-1700° C., and the sintering time may be, for example, set to 4-10 hours.

[0067] Step S500: annealing and surface treating the luminescent ceramic block to obtain luminescent ceramic.

[0068] The luminescent ceramic block is annealed in air, the annealing temperature is set to 1000-1300° C., the heat preservation time is set to 10-100 hours, and surface treatments such as grinding, polishing, and cutting are performed to obtain the luminescent ceramic.

[0069] The present application also proposes a wavelength conversion device, including a luminescent ceramic layer, wherein the luminescent ceramic layer is made of the luminescent ceramic of the above embodiment. The wavelength conversion device may be, for example, a fixed wavelength conversion device or a color wheel. Alternatively, the wavelength conversion device may be a reflective wavelength conversion device or a transmissive wavelength conversion device.

[0070] The present application also provides a light emitting device, comprising an excitation light source and a wavelength conversion device as described in the above embodiment. The light emitting device may include, for example, an illumination device, a projection device, an LD chip or an LED chip.

[0071] The solution of this application is described below with reference to specific embodiments:

[0072] Example 1

[0073] Follow Y 3 Al 5 O 12 :Ce stoichiometric ratio weighing nano-Al 2 O 3 , Y 2 O 3 、CeO 2 powder, wherein the molar doping concentration of Ce is 0.2%, and the Al 2 O 3 , Y 2 O 3 、CeO 2 The powder, ethyl orthosilicate and anhydrous ethanol were ball-milled and mixed to form a first slurry, which was then sintered at 1300°C for 3 hours, ground and sieved to obtain a fluorescent coating layer powder. 3 Al 5 O 12 :Ce phosphor particles, wherein the molar doping concentration of Ce is 0.5%, the fluorescent coating layer powder is mixed with the phosphor particles, and a polymer resin binder of 1% of the total volume of the powder is added, stirred and mixed for 2 hours, and then vacuum dried, ground, crushed and sieved to obtain coated phosphor powder. Prepare alumina powder with a particle size of 1μm, sintering aid ethyl orthosilicate, the sintering aid accounts for 1% of the total weight of the powder, and the mass ratio of alumina powder to phosphor particles is 7:3. The coated phosphor powder, alumina powder and sintering aid are mixed, dried, sieved, calcined at 800℃ for 3h, and then dry pressed at 10Mpa, and further processed at 100Mpa cold isostatic pressing to improve the density, and then pre-sintered at 1000℃ in air for 2h to obtain the first sintered body. Subsequently, the first sintered body was vacuum sintered at 1300° C. for 10 hours to obtain a luminescent ceramic block, and then annealed in air at 1000° C. for 50 hours, ground, polished and cut to obtain a luminescent ceramic.

[0074] Example 2

[0075] Follow Y 3 Al 5 O 12 :Ce stoichiometric ratio weighing nano-Al 2 O 3 , Y 2 O 3 、CeO 2 powder, wherein the molar doping concentration of Ce is 0.2%, and the Al 2 O 3, Y 2 O 3 、CeO 2 The powder, ethyl orthosilicate and anhydrous ethanol were mixed by ball milling to form a first slurry, and then sintered at 1300°C for 3 hours, ground and sieved to obtain a fluorescent coating layer powder. 3 Al 5 O 12 :Ce phosphor particles, wherein the molar doping concentration of Ce is 0.5%, the fluorescent coating layer powder is mixed with the phosphor particles, and a polymer resin binder of 1% of the total volume of the powder is added, stirred and mixed for 2 hours, and then vacuum dried, ground, crushed and sieved to obtain coated phosphor powder. Prepare alumina powder with a particle size of 1μm, sintering aid ethyl orthosilicate, the sintering aid accounts for 1% of the total weight of the powder, and the mass ratio of alumina powder to phosphor particles is 6:4. The coated phosphor powder, alumina powder and sintering aid are mixed, dried, sieved, calcined at 900℃ for 2h, and then dry pressed at 10Mpa, and further treated at 100Mpa cold isostatic pressing to increase the density, and then pre-sintered at 1000℃ in air for 2h to obtain the first sintered body. Subsequently, the first sintered body was vacuum sintered at 1500° C. for 4 hours to obtain a luminescent ceramic block, and then annealed at 1200° C. for 30 hours in air, ground, polished and cut to obtain a luminescent ceramic.

[0076] Example 3

[0077] Follow Y 3 Al 5 O 12 :Ce stoichiometric ratio weighing nano-Al 2 O 3 , Y 2 O 3 、CeO 2 powder, wherein the molar doping concentration of Ce is 0.2%, and the Al 2 O 3 , Y 2 O 3 、CeO 2 The powder, ethyl orthosilicate and anhydrous ethanol were ball-milled and mixed to form a first slurry, which was then sintered at 1300°C for 3 hours, ground and sieved to obtain a fluorescent coating layer powder. 3 Al 5 O 12:Ce phosphor particles, wherein the molar doping concentration of Ce is 0.5%, the fluorescent coating layer powder is mixed with the phosphor particles, and a polymer resin binder of 1% of the total volume of the powder is added, stirred and mixed for 2 hours, and then vacuum dried, ground, crushed and sieved to obtain coated phosphor powder. Prepare alumina powder with a particle size of 1μm, sintering aid ethyl orthosilicate, the sintering aid accounts for 1% of the total weight of the powder, and the mass ratio of alumina powder to phosphor particles is 7:3. The coated phosphor powder, alumina powder and sintering aid are mixed, dried, sieved, calcined at 1000℃ for 1h, and then dry pressed at 10Mpa, and further processed at 100Mpa cold isostatic pressing to improve the density, and then pre-sintered at 1100℃ in air for 1h to obtain the first sintered body. Subsequently, the first sintered body was vacuum sintered at 1700° C. for 4 hours to obtain a luminescent ceramic block, and then annealed at 1300° C. for 10 hours in air, ground, polished and cut to obtain a luminescent ceramic.

[0078] Example 4

[0079] Follow Y 3 Al 5 O 12 :Ce stoichiometric ratio weighing nano-Al 2 O 3 , Y 2 O 3 、CeO 2 powder, wherein the molar doping concentration of Ce is 0.5%, and the Al 2 O 3 , Y 2 O 3 、CeO 2 The powder, ethyl orthosilicate and anhydrous ethanol were mixed by ball milling to form a first slurry, and then sintered at 1300°C for 3 hours, ground and sieved to obtain a fluorescent coating layer powder. 3 Al 5 O 12:Ce phosphor particles, wherein the molar doping concentration of Ce is 0.5%, the fluorescent coating layer powder is mixed with the phosphor particles, and a polymer resin binder of 1% of the total volume of the powder is added, stirred and mixed for 2 hours, and then vacuum dried, ground, crushed and sieved to obtain coated phosphor powder. Prepare alumina powder with a particle size of 1μm, sintering aid ethyl orthosilicate, the sintering aid accounts for 1% of the total weight of the powder, and the mass ratio of alumina powder to phosphor particles is 6:4. The coated phosphor powder, alumina powder and sintering aid are mixed, dried, sieved, calcined at 900℃ for 2h, and then dry pressed at 10Mpa, and further treated at 100Mpa cold isostatic pressing to increase the density, and then pre-sintered at 1000℃ in air for 2h to obtain the first sintered body. Subsequently, the first sintered body was vacuum sintered at 1500° C. for 4 hours to obtain a luminescent ceramic block, and then annealed at 1200° C. for 30 hours in air, ground, polished and cut to obtain a luminescent ceramic.

[0080] Example 5

[0081] Follow Lu 3 Al 5 O 12 :Ce stoichiometric ratio weighing nano-Al 2 O 3 、Lu 2 O 3 、CeO 2 powder, wherein the molar doping concentration of Ce is 0.2%, and the Al 2 O 3 、Lu 2 O 3 、CeO 2 The powder, ethyl orthosilicate and anhydrous ethanol were mixed by ball milling to form a first slurry, and then sintered at 1300°C for 3 hours, ground and sieved to obtain a fluorescent coating layer powder. 3 Al 5 O 12:Ce phosphor particles, wherein the molar doping concentration of Ce is 0.5%, the fluorescent coating layer powder is mixed with the phosphor particles, and a polymer resin binder of 1% of the total volume of the powder is added, stirred and mixed for 2 hours, and then vacuum dried, ground, crushed and sieved to obtain coated phosphor powder. Prepare alumina powder with a particle size of 1μm, sintering aid ethyl orthosilicate, the sintering aid accounts for 1% of the total weight of the powder, and the mass ratio of alumina powder to phosphor particles is 6:4. The coated phosphor powder, alumina powder and sintering aid are mixed, dried, sieved, calcined at 900℃ for 2h, and then dry pressed at 10Mpa, and further treated at 100Mpa cold isostatic pressing to increase the density, and then pre-sintered at 1000℃ in air for 2h to obtain the first sintered body. Subsequently, the first sintered body was vacuum sintered at 1500° C. for 4 hours to obtain a luminescent ceramic block, and then annealed at 1200° C. for 30 hours in air, ground, polished and cut to obtain a luminescent ceramic.

[0082] It should be noted that the various optional implementations introduced in the embodiments of the present application can be implemented in combination with each other or can be implemented separately, and the embodiments of the present application are not limited to this.

[0083] In the description of the present application, it should be understood that the terms "upper", "lower", "left", "right", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, and a specific orientation structure and operation. Therefore, it cannot be understood as a limitation on the present application. In addition, "first" and "second" are only for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present application, unless otherwise specified, "multiple" means two or more.

[0084] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", etc. should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0085] The above embodiments are described with reference to the accompanying drawings, and other different forms and embodiments are also feasible without departing from the principles of the present application, so the present application should not be constructed as a limitation of the embodiments proposed herein. More specifically, these embodiments are provided so that the present application will be perfect and complete, and the scope of the present application will be conveyed to those skilled in the art. In the accompanying drawings, the component sizes and relative sizes may be exaggerated for clarity. The terms used herein are only based on the purpose of describing specific embodiments and are not intended to be limiting. The terms "comprising" and / or "including" when used in this specification indicate the presence of the features, integers, components and / or components, but do not exclude the presence or increase of one or more other feature integers, components, components and / or their groups. Unless otherwise indicated, when stated, the numerical range includes the upper and lower limits of the range and any sub-ranges therebetween.

[0086] The above descriptions are only some embodiments of the present application, and do not limit the protection scope of the present application. Any equivalent device or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A luminescent ceramic, characterized in that: It comprises phosphor crystal grains, a phosphor coating layer, matrix ceramic crystal grains and pores; the phosphor coating layer envelops the periphery of the phosphor crystal grains, and at least part of the phosphor crystal grains is combined with the matrix ceramic crystal grains through the phosphor coating layer; at least part of the pores are located between a plurality of the matrix ceramic crystal grains or / and between the matrix ceramic crystal grains and the phosphor coating layer.

2. The luminescent ceramic according to claim 1, characterized in that: The fluorescent coating layer includes a first matrix phase doped with a first luminescent ion; the fluorescent powder grains include a second matrix phase doped with a second luminescent ion; the first luminescent ion is the same as or different from the second luminescent ion; or / and the first matrix phase is the same as or different from the second matrix phase.

3. The luminescent ceramic according to claim 2, characterized in that: The molar doping concentration of the first luminescent ions is 0.02% to 5%; or / and the molar doping concentration of the second luminescent ions is 0.01% to 10%.

4. The luminescent ceramic according to any one of claims 1 to 3, characterized in that: The molar doping concentration of the first light-emitting ions is less than the molar doping concentration of the second light-emitting ions.

5. The luminescent ceramic according to any one of claims 1 to 3, characterized in that: The first matrix phase and the second matrix phase are oxide garnet phases; the first luminescent ions and the second luminescent ions are cerium ions.

6. The luminescent ceramic according to claim 1, characterized in that: The volume content of the phosphor particles is 30% to 90%; Or / and the particle size of the phosphor crystal particles is 1-10 um.

7. The luminescent ceramic according to claim 1, characterized in that: The percentage of the pores in the total volume of the luminescent ceramic is 2-20%; Or / and the pore size is 0.1-2 um.

8. A method for preparing a luminescent ceramic, characterized in that: The preparation method comprises: preparing raw materials for a fluorescent coating layer, mixing, sintering and crushing the raw materials for the fluorescent coating layer to obtain a fluorescent coating layer powder; Preparing phosphor crystals, mixing the phosphor crystals with phosphor coating layer powder to obtain coated phosphor crystals; preparing a matrix ceramic powder and a sintering aid, mixing, molding and pre-sintering the coated phosphor grains, the matrix ceramic powder and the sintering aid to obtain a first sintered body; Sintering the first sintered body to obtain a luminescent ceramic block; The luminescent ceramic block is annealed and surface treated to obtain the luminescent ceramic.

9. A wavelength conversion device, characterized in that: The invention comprises a luminescent ceramic layer, wherein the luminescent ceramic layer is made of the luminescent ceramic according to any one of claims 1 to 7.

10. A light emitting device, characterized in that: It comprises an excitation light source and the wavelength conversion device as claimed in claim 9.